COVID-19, Economic Growth, and Income Inequality: Empirical Study in Indonesia - Lestari Agusalim; Yoga Setiawan (Economics Development Analysis Journal, 2024)
Income inequality remains a significant issue in developing countries like Indonesia, affecting societal well-being unevenly. Economic growth is often considered a key indicator of social welfare, but its benefits are not always distributed equitably. When economic growth coincides with high levels of income inequality, it suggests that only certain groups reap greater benefits while others are left behind. Therefore, it is essential to analyze whether there are disparities in the influence of economic growth on income inequality in Indonesia before and during the COVID-19 pandemic. Using a random effects model and 12 years of data (2010–2021), this analysis reveals that economic growth does not significantly affect income inequality in Indonesia, challenging the Kuznets hypothesis. Domestic investment (DIN) also shows no influence on income inequality. In contrast, the human development index (HDI) consistently has a significant negative impact on income inequality across both periods. Meanwhile, foreign direct investment (FDI) positively impacts income inequality. There is no difference in the influence of HDI and FDI on income inequality before and during COVID-19. These findings emphasize the importance of improving human resource quality as an effective strategy for addressing income inequality, particularly by enhancing access to education, healthcare services, and overall social welfare.